A beryllium-free deep-UV nonlinear optical material CsNaMgP2O7 with honeycomb-like topological layers. Issue 15 (28th March 2018) - Zhao, Sangen; Yang, Yi; Shen, Yaoguo; Wang, Xiaodong; Ding, Qingran; Li, Xianfeng; Li, Yanqiang; Li, Lina; Lin, Zheshuai; Luo, Junhua
Abstract : Beryllium-free deep-UV nonlinear optical CsNaMgP2 O7 consists of honeycomb-like topological layers, which should be attributable to an enhanced second harmonic generation response. Abstract : Few nonlinear optical (NLO) materials are available for deep-UV second-harmonic generation (SHG), limited by the fundamental requirements of the structure-directing optical properties. KBe2 BO3 F2 is the sole exception, but it suffers from the high toxicity of the compositional beryllium element and a serious layering growth tendency. Here, we report a beryllium-free deep-UV NLO phosphate with honeycomb-like topological structural layers, namely, CsNaMgP2 O7 . The phosphate exhibits an enhanced SHG response of 1.1 times that of KH2 PO4, which is comparable to that of KBe2 BO3 F2 . Based on theoretical analysis, the enhanced SHG response can be well rationalized. Meanwhile, CsNaMgP2 O7 possesses a reinforced interlayer bonding of about 2.95 times that of KBe2 BO3 F2, which is very favorable to mitigate the layering growth tendency. This work will be helpful to better understand the structure–property relationships in deep-UV NLO materials.